TRANSLATION METHODS OF UZBEK PHRASEOLOGICAL UNITS INTO ENGLISH (Spectrum Journal of Innovation, Reforms and Development, 2025)
The translation of Uzbek phraseological units (PUs) into English presents complex challenges rooted in linguistic, structural, and cultural differences. PUs—encompassing idioms, proverbs, and fixed expressions—are inherently non-compositional, requiring strategies beyond literal translation to preserve meaning and cultural nuance. This paper explores key difficulties in translating Uzbek PUs, such as cultural specificity, grammatical divergence, the absence of direct equivalents, and connotative subtleties. It also outlines common translation strategies, including direct equivalence, loan translation, functional equivalence, paraphrasing, adaptation, and compensation. Through illustrative examples, the study demonstrates how these strategies are applied in practice. Additionally, it discusses the role of cultural competence, bilingual dictionaries, and computational tools like cross-lingual text classification and bilingual lexicon induction in supporting translation efforts. The paper concludes by emphasizing the critical need for culturally informed, context-sensitive approaches to PU translation in an increasingly globalized world.